Influence Of Media Viewing Habits On Attitude Towards Aggression Among Schoolboys At International Schools In Kuala Lumpur. - Azarian, Zoheir Sabaghpour (2009)

(untitled)
Violence is one of the global concerns today in all segments of the world. Antisocial behavior in human beings is accepted to be associated to a number of physiological, psychological, domestic, and cultural aspects. The learning environments which a child is exposed are also assumed to contribute to the increase of aggressive behavior and attitudes. Media violence as one of specific learning condition is believed to be a potential contributor to the growth of antisocial behavior in children and youth. Many studies have been conducted in the area of media violence and its effects on the young viewers. A major focus has been the relationship between media violence and aggressive behavior but, interestingly, research regarding the relationship between media violence and attitudes about aggression is limited. The purpose of this study, therefore, was to contribute to the state of the research by predicting and comparing attitudes about aggression among adolescent boys on the basis of their exposure to violence in movies.